2015
DOI: 10.1080/09397140.2015.1020611
|View full text |Cite
|
Sign up to set email alerts
|

Records of ants (Hymenoptera: Formicidae) from Northern Iran

Abstract: The results of ant collecting in two hitherto unsampled areas of Iran, the north eastern province of Khorasan Razavi and the north western Zanjan Province are reported. Both areas fall within lacunae of knowledge on previous distribution. Species previously not known from Iran are Aphaenogaster holtzi, Camponotus (Myrmentoma) rebeccae, Cataglyphis albicans, Cataglyphis rockingeri, Lasius himalayanus and Proformica ferreri.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Due to its location, geography, and predominance of open and arid habitats, Iran hosts the highest number of Cataglyphis worldwide (Paknia et al 2008, Janicki et al 2016. So far, there are 32 species of the genus known from the county, but some records need verification and confirmation (Paknia et al 2008(Paknia et al , 2009Moradloo et al 2015;Rad et al 2018). The present work is a contribution to the understanding of the Iranian Cataglyphis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its location, geography, and predominance of open and arid habitats, Iran hosts the highest number of Cataglyphis worldwide (Paknia et al 2008, Janicki et al 2016. So far, there are 32 species of the genus known from the county, but some records need verification and confirmation (Paknia et al 2008(Paknia et al , 2009Moradloo et al 2015;Rad et al 2018). The present work is a contribution to the understanding of the Iranian Cataglyphis.…”
Section: Introductionmentioning
confidence: 99%
“…Iran, due to its location and predominance of open and arid habitats, hosts one of the highest numbers of Cataglyphis species. So far, there are 35 Cataglyphis taxa recorded for this country, but some records need confirmation or correction (Paknia et al 2008(Paknia et al , 2009Moradloo et al 2015;Janicki et al 2016;Rad et al 2018;Khalili-Moghadam et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Paknia et al (2008) listed 110 species in 26 genera and six subfamilies (Aenictinae, Dolichoderinae, Dorylinae, Formicinae, Myrmicinae, and Ponerinae) as the fauna of Iran. Several dozen works have been published (Tirgari & Paknia 2004, Paknia 2006, Paknia & Kami 2007, Ghahari et al 2009, Rafinejad et al 2009, Paknia 2010, Firouzi et al 2011, Ghahari et al 2011, Mohammadi et al 2012, Hossein Nezhad et al 2012, Kiran et al 2013, Shiran et al 2013, Ghahari et al 2015, Khandehroo et al 2015, Mirzamohamadi et al 2015, Moradloo et al 2015, Mortazavi et al 2015, Ghobadi et al 2016, Heidari et al 2017, Pashaei Rad et al 2018, Khalili-Moghadam et al 2019, Mohseni Rad et al 2019, Salata et al 2020, and currently, more than 200 species of ants have been reported from Iran. The aim of this paper is a faunistic study on Formicidae from North and Northwestern regions of Iran, and introducing of four species as new records for the Iranian fauna.…”
Section: Introductionmentioning
confidence: 99%